A Secure Learning Environment Framework of Virtual Reality Application for TVET Education Using Blockchain Technology - Rosli, Athirah; Shahrin, Suhaimi; Awang, Hapini (Multidisciplinary Applied Research and Innovation, 2023)
The epidemic of COVID-19 has altered the environment in several areas, including education. One of the impacted education sectors is Technical and Vocational Education Training (TVET), which is one of the key drivers of the Eleventh Malaysian Plan. Problems arise when learning processes, assessments, and management are needed to be carried out online. The safety of the Internet is a major concern for universities, teachers, and students. This project presents a blockchain-based theoretical framework for VR applications in higher education and TVET. The use of VR can be considered as a psychological motorized acquisition device that provides an effective online learning experience. Measurement of learning results is performed from a virtual reality simulator using Head Mounted Display (HMD). Through online distance learning, everything is put in the cloud, and everyone can access it. Blockchain, a distributed ledger that records network transactions and data, prevents unauthorized changes. The university administration that offers TVET courses will get to manage and monitor the ODL between student and lecturer without interfering with the process.  Any updates on the marks and assessment are recorded and can be viewed in real-time. University administrators manage to reduce expenses and labor for system and internet security. VR will incorporate blockchain technology. This method will make blockchain a possible tool for securing cloud data. Thus, TVET education management, students, and lecturers may have improved learning experiences without worrying about virtual reality safety.